Service-Oriented Organizational Citizenship Behavior, Service Quality and Customer Citizenship Behavior: Comparison of Implementation and Evaluation from the Perspective of Bank Customers - Soni Harsono; Harry Widyantoro; Tjahjani Prawitowati; Basuki Rachmat (Tržište, 2021)
Purpose – This study aims to explore the effect of service-oriented organizational citizenship behavior (SOCB) on service quality and to compare SOCB, service quality, and customer citizenship behavior (CCB) between two banks. Design/Methodology/Approach – The research method is an associative and comparative approach involving 271 bank customers and 30 bank employees in a survey, using a questionnaire as the primary data collection tool. The analytical tool used is linear regression, with the Mann-Whitney employed to test the data from two independent samples. Findings and implications – This study proves that SOCB has a significant positive effect on service quality in all banks. There is no observable difference in SOCB, service quality, or CCB assessment between the bank whose employees are given training and the bank whose employees are not given training. There is an increase in employee knowledge after attending the training, specifically an increase in the SOCB score. Changes in employee behavior and skills related to SOCB and service quality can also be observed. Limitations – This study focuses on SOCB and service quality only while not examining the relationship between satisfaction and CCB, which should be done in theory. The number of research participants is not the same for the two banks. Originality – While the research study begins with customer evaluation of the banking employees’ SOCB and service quality, its results are then taken into consideration in training. The training results are finally re-evaluated by customers and compared with other banks.